Frailty index to covid-19: A case study of the impact of the disease in the mucuri valley (Research, Society and Development, 2021)
Planet Earth is going through yet another pandemic in history, this time coming from the SARS-CoV-2 virus called COVID-19. Brazil is one of the most affected countries and one of the world leaders in number of infected and in deaths. Brazilian regions are more susceptible or resistant to the disease due to several social, environmental and economic factors. Thus, the objective was to obtain an index to measure the situation of municipalities in the northeastern region of Minas Gerais, with regard to the dissemination/impact of COVID-19 using simplified data. For that, the main indicators available in the IBGE and dataSUS database that they keep in relation to a COVID-19 were listed. For its validation, the proposed index was compared with other indicators and numbers related to infection and deaths. Also, a case study was carried out in the Mucuri valley region, which has 27 municipalities in the northeast of Minas Gerais. It can be observed that the index is not related to the others economic index. Nevertheless, the index is suitable to verify the impact of the pandemic in the cities of the Vale do Mucuri region, as well as demonstrating evidence of the predictability of the impact of COVID-19 among the municipalities.